2015 AIChE Spring Meeting & 11th Global Congress on Process Safety : 49th Annual Loss Prevention Symposium (LPS) (Center for Chemical Process Safety/AIChE, 2015)
This book is one of four parallel symposia that comprise GCPS. Organized by Group 11A of the AIChE Safety and Health (S&H) Division, the LPS has been held annually since 1967. The Symposium promotes process safety by providing a forum for practitioners from the chemical industry, allied industries, academia, and government to share technological advances in process safety, explosion prevention, and fire protection as well as to share the lessons learned from incident investigations. The Symposium consists of six sessions, each with at least six 30-minute presentations. -- Provided by publisher.
Keywords: Chemical process control.; Chemical plants -- Safety measures.; elektronické knihy; electronic books